Epidemiology of uveal melanomas in Moscow - E. E. Grishina; M. Yu. Lerner; E. G. Gemdzhian (Alʹmanah Kliničeskoj Mediciny, 2017)
Rationale: Melanoma of the uveal tract of the eye is among the most prevalent malignant intraocular tumors.Aim: To identify epidemiological characteristics of uveal melanoma in Moscow.Materials and methods: We performed a retrospective analysis of out-patient files and follow-up charts of patients with uveal melanoma in the Ophthalmological Clinical Hospital of the Department of Healthcare, Moscow, from 1977 to 2012.Results: Within 36 years, 2547 patients with uveal melanoma have been registered, at the age of 16 to 92 years. The male to female ratio was 1:1.5. The rate of patient referrals with subsequent diagnosis of uveal melanoma has not changed from 1977 to 2000 and was on average 1.07 persons per 100,000 of the adult population. From 2001 to 2012, there was some decline in the number of referrals with uveal melanoma to the average of 0.9 persons per 100,000 of the adult population. We analyzed survival among 359 patients with uveal melanoma after enucleation surgery of the eye; 37% of them were men (63.2 ± 1.8 years) and 63% women (69.5 ± 2.7 years). Their 5-year metastasis-free survival was 65 ± 3%, whereas the 7-year survival was 60 ± 4%. The mean time to death was 5.5 years. There were no association between the life longevity and patients gender, but their survival was associated with the age of patients. The risk of death from metastatic uveal melanoma among patients above 60 years of age was on average 10% higher. After the enucleation surgery, patients with Т4 melanoma lived significantly less than those with Т1-3 tumor (5 and 6.5 years, respectively; р = 0.05).Conclusion: The rates of diagnosis of uveal melanoma at referrals within 36 years did not increased. Epidemiology of uveal melanoma in Moscow is characterized by a high proportion of elderly women. Shorter overall and metastasis-free survival of patients with uveal melanoma after the enucleation surgery depends from a higher proportion of elderly people in the regional population and late diagnosis of the disease.